Ureaplasma Urealyticum Infection Contributes to the Development of Pelvic Endometriosis Through Toll-Like Receptor 2 - Noh, Eui Jeong; Kim, Dong Jae; Lee, Jun Young; Park, Jong Hwan; Kim, Jong-Seok; Han, Jae Won; Kim, Byoung Chan; Kim, Chul Jung; Lee, Sung Ki (Frontiers in Immunology, 2019)
Endometriosis is a chronic gynecological disorder, characterized by the presence of ectopic endometrial tissue outside the uterine cavity. Among several hypotheses, Sampson’s theory of retrograde menstruation is still applicable. Recent studies have reported the importance of inflammation among endometrial tissue, the peritoneum, and immune cells. However, less is known regarding the role of bacterial infection in the pathophysiology of endometriosis. We hypothesized that U. urealyticum infection might contribute to the development of endometriosis by inducing the production of inflammatory mediators by peritoneal mesothelial cells (PMCs), possibly through TLR2. Hence, our objective was to reveal whether PMC infection by U. urealyticum is associated with endometriosis. Moreover, we aimed to demonstrate the molecular mechanism involved in this relationship. We developed a new infection-induced mouse model of endometriosis with wild type and Tlr2-deficient mice. Based on the in vivo mouse model, U. urealyticum-infected mice showed significantly increased numbers and sizes of ectopic endometriotic lesions. U. urealyticum upregulated not only the production of IL-6, CXCL1, and CCL2, but also the expression of ICAM-1, VCAM-1, and MMP2 in murine PMCs. This series of inflammatory responses in PMCs was mediated mainly through TLR2. The phosphorylation of ERK and JNK was observed when U. urealyticum was added to PMCs and knock out of Tlr2 inhibited these MAPKs phosphorylation. Based on our co-culture study, U. urealyticum-infected PMCs exhibited significantly increased attachment to ESCs compared with uninfected PMCs. Collectively, U. urealyticum infection promotes the development of endometriosis by increasing inflammatory mediators, adhesion molecules, and MMP-2 expression in PMCs through TLR2 signaling. Through our results, we present a theory that infection-induced pelvic inflammation contributes to the initiation and progression of endometriosis. Appropriate treatment of reproductive tract infection may decrease the prevalence of endometriosis.